Digital storytelling : capturing lives, creating community - Lambert, Joe; Hessler, H. Brooke (Routledge, 2018)
"StoryCenter founder Joe Lambert offers budding storytellers the skills and tools they need to craft compelling digital stories. Using a "seven steps" approach, Lambert helps storytellers identify the fundamentals of dynamic digital storytelling -- from conceiving a story, to seeing, assembling, and sharing it. Readers will also find new explorations of the global applications of digital storytelling in education and other fields, as well as additional information about copyright, ethics, and distribution. The book is filled with resources about past and present projects on the grassroots and institutional level, including new chapters specifically for students and a discussion of the latest tools and projects in mobile device-based media"- Resumé vydavatel
Previous edition: 2013.
Keywords: vyprávění; tvůrčí psaní; interaktivní multimédia; storytelling; creative writing; interactive multimedia; monografie; elektronické knihy; monographs; electronic books